Diagnosis, treatment and clinical outcomes of extrauterine sites of leiomyomatosis: a systematic review - Jacopo Di Giuseppe; Leonardo Natalini; Mila Bordini; Daniele Crescenzi; Linda Grementieri; Jessica Petrucci; Arianna Asaro; Luca Giannella; Giovanni Delli Carpini; Camilla Grelloni; Andrea Ciavattini (Annals of Medicine)
Background This review aims to provide a comprehensive description of the clinical presentation, treatment, and histopathological features of extrauterine sites of leiomyomatosis (ESL), such as disseminated peritoneal leiomyomatosis (DPL), parasitic myoma (PM), benign metastatic leiomyoma (BML), and intravascular leiomyoma (IVL). The impact of previous surgery (hysterectomy or myomectomy) on development of intra-abdominal extrauterine leiomyomas (IAELs) and extra-abdominal extrauterine leiomyomas (EAELs) has been evaluated.Methods According to PRISMA guidelines, we searched PubMed, Scopus, and Web of Science databases. Relevant articles were retrieved in full-text format and screened based on predefined inclusion and exclusion criteria.Results 358 studies (372 cases) are included. Among IAELs, the most common symptom is abdominopelvic pain (63.9% of DPL, and 69.2% of PMs cases, respectively). In contrast, EAELs exhibit heterogeneous clinical presentations; dyspnea is the most common symptom (29.7% of BML, and 29.9% of IVL cases, respectively). 68.8% of DPL, 60% of PM, 89.7% of BML, and 56.4% of IVL patients underwent previous uterine surgery. A significant association (p = 0.0417) between the type of previous uterine surgery (hysterectomy and myomectomy) and the subsequent location of ESLs is found (68.7% VS 51.4% in EAELs, 31.3% VS 48.6% in IAELs, respectively).Conclusions DPL, PM, BML, and IVL exhibit overlapping characteristics, requiring a multimodal approach that includes imaging, histopathology, and surgical or medical management. Greater awareness among clinicians is needed regarding surgical procedures involving ligation and/or cutting of major uterine vessels, which appear to contribute to the development of EAELs, and morcellation, which tends to promote intraperitoneal metastatic spread.